The development of American economic warfare in World War II, 1940-1941 - Richards, Robert Benjamin (My University, 2025)
This dissertation examines the development of American economic warfare during World War II, focusing on the critical years of 1940-1941. During this period, military and civilian leaders responsible for the development and direction of economic strategy conceived, built, and employed economic warfare capabilities as an integral part of American grand strategy. Since 1959, no historian has comprehensively analyzed America's complete World War II economic warfare campaign, and no published historical work has thoroughly explained its origins. Existing scholarship is fragmented—chronologically silent for over 75 years, British-centric, and overshadowed by studies of strategic bombing and submarine campaigns—leaving the role of economic warfare in U.S. grand strategy unexplored. Utilizing largely untapped archival records from the US Foreign Economic Administration (RG 169), this dissertation provides the first US-focused analysis and reestablishes economic warfare within the history of the US and Allied grand strategy. The evidence presented in this dissertation supports four key findings. First, although often overlooked by historians, economic warfare was a core component of US grand strategy by at least July 1940. Second, in July 1940, President Franklin D. Roosevelt established the Office of the Administrator of Export Control to conduct a steadily expanding economic warfare campaign that, by August 1941, had largely cut the Axis Powers off from sources of strategic raw materials in Latin America and significant parts of Asia. Third, while both derived from their respective experiences with the “blockade” in World War I, US economic warfare theory, doctrine, and organization developed independently of British economic warfare theory and practice. Finally, contrary to post-World War II assessments, both the American and combined American-British economic warfare campaigns were efficient and effective in reducing the number of suitable, feasible, or acceptable strategic options available to Germany and Japan. The economic warfare campaigns began to significantly impact Axis capabilities, resources, and morale starting in early 1941.
Keywords: Economic warfare; Grand strategy; World War II; Strategy; Economic defense; Warfare